'Behind the drug scene'. Issue 26 (19th December 1969) - Unknown
Abstract : Last month the BMA published an excellent Family Doctor booklet on drug dependence. The Editor's claim in the foreword is not an exaggeration: it is indeed a unique, and valuable, contribution to public understanding of this complex subject. Five short chapters deal with different aspects: the background to the drug scene (Michael Schofield); the drugs involved (C.R.B. Joyce); the drug taker's personality (Martin Mitcheson); drug takers and the community (David Downes); and 'If you need help' (Peter Chapple). The booklet should be regarded as essential reading for sixth-formers and students, and their elders, and doctors can help to draw attention to it.